2006
DOI: 10.4049/jimmunol.177.7.4749
|View full text |Cite
|
Sign up to set email alerts
|

Basal Rather Than Induced Heme Oxygenase-1 Levels Are Crucial in the Antioxidant Cytoprotection

Abstract: Heme oxygenase-1 (HO-1) overexpression protects against tissue injury in many inflammatory processes, including ischemia/reperfusion injury (IRI). This study evaluated whether genetically decreased HO-1 levels affected susceptibility to liver IRI. Partial warm ischemia was produced in hepatic lobes for 90 min followed by 6 h of reperfusion in heterozygous HO-1 knockout (HO-1+/−) and HO-1+/+ wild-type (WT) mice. HO-1+/− mice demonstrated reduced HO-1 mRNA/protein levels at baseline and postreperfusion. This cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 48 publications
4
49
0
Order By: Relevance
“…13, 23 The present study demonstrates that HO-1 expression in macrophages constitutes an important component of We and others have previously demonstrated that HO-1 ϩ/Ϫ mice can serve as an in vivo model of decreased HO-1 expression. Livers from HO-1 ϩ/Ϫ mice exhibit Ϸ32% baseline mRNA and Ϸ41% protein of WT littermates, 24 similar to hearts from HO-1 ϩ/Ϫ mice, which also showed 41% protein compared with WT littermates. 25 Decreased HO-1 expression levels resulted in a proportional reduction in tissue HO enzyme activity (supplemental Figure I) and significant aggravation of outcomes in models of liver 24 and cardiac 25 ischemia reperfusion, where the reintroduction of ROS after a period of ischemia plays a predominant pathogenic role.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…13, 23 The present study demonstrates that HO-1 expression in macrophages constitutes an important component of We and others have previously demonstrated that HO-1 ϩ/Ϫ mice can serve as an in vivo model of decreased HO-1 expression. Livers from HO-1 ϩ/Ϫ mice exhibit Ϸ32% baseline mRNA and Ϸ41% protein of WT littermates, 24 similar to hearts from HO-1 ϩ/Ϫ mice, which also showed 41% protein compared with WT littermates. 25 Decreased HO-1 expression levels resulted in a proportional reduction in tissue HO enzyme activity (supplemental Figure I) and significant aggravation of outcomes in models of liver 24 and cardiac 25 ischemia reperfusion, where the reintroduction of ROS after a period of ischemia plays a predominant pathogenic role.…”
Section: Discussionmentioning
confidence: 71%
“…Differences in HO-1 expression levels did not result in any compensatory changes in HO-2 mRNA ( Figure 1B). Decreased HO-1 expression in HO-1 ϩ/Ϫ macrophages paralleled decreased tissue expression of HO-1 in these systemic KO mice in livers, 24 spleens, heart, kidney, and aorta (data not shown). Decreased and absence of HO-1 expression resulted in a concomitant reduction in tissue HO enzyme activity, as demonstrated in liver microsomes from HO-1 ϩ/Ϫ and HO-1 Ϫ/Ϫ mice (supplemental Figure I).…”
Section: Ros Generationmentioning
confidence: 95%
“…Indeed, the beneficial effects of HO-1 on various inflammatory diseases (e.g., RA, colitis and ischemia/reperfusion injury) have been reported. [19][20][21][22][23] Choi et al 15) have reported that CO suppressed the production of such pro-inflammatory cytokines as TNF-, IL-1, MIP-1 and MIP-2 in activated macrophages. In fact, AB inhibited the generation of these cytokines in LPS-stimulated human monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Ad-HO-1 overexpression also prevented CD95/FasL-mediated apoptosis, thereby improving liver function (69,70). Recently, a warm liver IRI model using wild-type and heterozygous HO-1-deficient (HO-1 +/-) mice demonstrated that basal HO-1 levels are more important than the upregulation of HO-1 in response to IR (71). Pretreatment with inhaled anesthetic isoflurane has also shown hepatoprotection in liver IRI, through increasing local HO-1 mRNA/protein expression and HO-1 enzyme activity (72).…”
Section: Ho Systemmentioning
confidence: 99%